IMPLEMENTASI MANAJEMEN KURIKULUM DALAM MENINGKATKAN MUTU PENDIDIKAN - Primanita Sholihah Rosmana; Sofyan Iskandar; Atikah Putri; Azeera; Nurul Fitriyani Roisussalamah (JURNAL BIOSHELL, 2022)
This study aims to examine curriculum management in an effort to improve the quality of education. This research uses a literature study method. The purpose of this article is to see how developed curriculum management is in an effort to improve quality in education. To improve curriculum management, it must be supported by various parties, such as the government, the community, and educators. Curriculum management will not be satisfactory if it is made in a crude way or follows instructions that are less relevant. To achieve a good and regular educational curriculum activity, it must be made with full consideration from various parties. The curriculum must have quality improvements that can bring the world of education better. This has to do with the demands of the curriculum, it is better for local governments and at lower levels such as schools to have the freedom to program in the education curriculum.